2014
DOI: 10.1051/matecconf/20141501023
|View full text |Cite
|
Sign up to set email alerts
|

Construction Site Workers’ Awareness on Using Safety Equipment: Case Study

Abstract: Abstract. Construction sector is an important sector and contributed significantly to national development. However, this sector poses higher risk to accident. This is due to fact that construction site can be considered as a dangerous zone to workers and to the public. Due to the variety of cases occurs on site, the contractor will usually have to pay the cost related to accidents in the form of higher insurance premium. Despite various measures, accidents still occur at construction sites. Personal Protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…A study in Malaysia had found similar results. 11 In the Malaysian study, most of the participants were below 40 years old and only 1% were over 48. A study in Nepal also found similar characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…A study in Malaysia had found similar results. 11 In the Malaysian study, most of the participants were below 40 years old and only 1% were over 48. A study in Nepal also found similar characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…The alarming rate of scaffolding accidents led to a special committee (the Position Paper Committee) in 2013 by the Institution of Engineers Malaysia (The Institution of Engineers, Malaysia, 2015). Yet, there have been more studies and reports on accidents relating to scaffolding on construction sites in Malaysia (Abas et al, 2020;Ayob et al, 2018;Williams et al, 2017;Ulang et al, 2014;Keng and Abdul Razak, 2014;Lee et al, 2018;CIDB, 2018). As much as the findings and recommendations for the studies are helpful, the studies tend not to go into the level of detail necessary to provide systemic explanations of the causes and remedial actions required for scaffolding accidents on construction sites.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in China, Chia-Fen and collaborators determined that the smallest construction companies presented a higher incidence of falls from heights owing to a lack of experience, of training and the generalized practice of not using personal or collective protection equipment [ 51 ]. In this regard, various authors have reported that not using personal or collective protection equipment is a major source of accidents in the construction sector [ 18 , 21 , 22 ]. Regarding the work clothing used by workers in Guatemalan construction, 37.0% of companies reported that they use T shirts and hi-viz jackets, 16.0% T shirts, hi-viz jackets, and a uniform or canvas trousers, 14.0% use only hi-viz jackets and 12.0% T shirts and a uniform or canvas trousers.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Arévalo indicates that knowing the economic repercussion of accidents, from the design phase and its prevention measures, would make it possible to delimit a more efficient security management system in the company from its origin, as well as deepen the prevention and study of accidents, and provide enough personal protection equipment (PPE) [ 16 ]. Complying with PPE use and availability, which may depend on the size of the organization and the type of training for its use [ 17 ], as well as other security measures, is required to reduce injuries and fatal accidents among construction workers [ 18 , 19 , 20 ] or among visitors to the construction site [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%